Metabolite database for root, tuber, and banana crops to facilitate modern breeding in understudied crops. (22nd January 2020) - Price, Elliott J.; Drapal, Margit; Perez‐Fons, Laura; Amah, Delphine; Bhattacharjee, Ranjana; Heider, Bettina; Rouard, Mathieu; Swennen, Rony; Becerra Lopez‐Lavalle, Luis Augusto; Fraser, Paul D.
Summary: Roots, tubers, and bananas (RTB) are vital staples for food security in the world's poorest nations. A major constraint to current RTB breeding programmes is limited knowledge on the available diversity due to lack of efficient germplasm characterization and structure. In recent years large‐scale efforts have begun to elucidate the genetic and phenotypic diversity of germplasm collections and populations and, yet, biochemical measurements have often been overlooked despite metabolite composition being directly associated with agronomic and consumer traits. Here we present a compound database and concentration range for metabolites detected in the major RTB crops: banana ( Musa spp.), cassava ( Manihot esculenta ), potato ( Solanum tuberosum ), sweet potato ( Ipomoea batatas ), and yam ( Dioscorea spp . ), following metabolomics‐based diversity screening of global collections held within the CGIAR institutes. The dataset including 711 chemical features provides a valuable resource regarding the comparative biochemical composition of each RTB crop and highlights the potential diversity available for incorporation into crop improvement programmes. Particularly, the tropical crops cassava, sweet potato and banana displayed more complex compositional metabolite profiles with representations of up to 22 chemical classes (unknowns excluded) than that of potato, for which only metabolites from 10 chemical classes were detected. Additionally, over 20% of biochemical signatures remained unidentified for every crop analyzed. Integration of metabolomics with the on‐going genomic and phenotypic studies will enhance 'omics‐wide associations of molecular signatures with agronomic and consumer traits via easily quantifiable biochemical markers to aid gene discovery and functional characterization. Significance Statement: A metabolite‐specific database cataloguing the biochemical diversity within and between root, tuber, and banana (RTB) crops has been compiled from profiling thousands of accessions. The database records the extent of metabolite concentrations available in screened germplasm of each RTB crop and therefore can be used to set breeding targets. This information aids in crop breeding programmes to improve the livelihoods for more than two billion people reliant on RTB crops.